Using a novel spiral-filter press technology to biorefine horticultural by-products: The case of tomato. Part II: Evaluation of the process impact on the physical tomato juice quality. (December 2016) - Kips, Lies; De Paepe, Domien; Bernaert, Nathalie; Van Weyenberg, Stephanie; Van Pamel, Els; De Loose, Marc; Raes, Katleen; Van Droogenbroeck, Bart
Abstract: The spiral-filter press offers potential to minimize food losses by allowing the biorefinery of a multitude of food waste matrices into qualitative, healthy food products such as a cloudy juices and other derived products. This part of the study (part II) focuses on the effect of different unit operations on the physical juice quality, which is illustrated for tomato biomass. Using optimized process conditions (part I), a physically and microbiologically stable juice with a high juice yield (97.9 ± 0.2%) was obtained. Thereby, the intense red color of the tomato was preserved throughout the process. Furthermore, by varying the process conditions as well as tomato cultivar, juices with different physical stabilities, turbidities and particle size distributions were produced, indicating the flexibility of the spiral-filter press to produce different end-products. Industrial relevance: This pilot-scale study shows the potential of the spiral-filter press for processing biomass into qualitative products. Although this technology is emerging and has already drawn the attention of the industry in Europe and beyond, limited scientific data are available where process impact on yield, quality and stability is described in detail. Hence, data bridging this scientific insight with relevant industrial applications is crucial for optimal use of this novel technology. Highlights: A novel tomato juice production process was tested using a spiral filter press. This resulted in a physically and microbiologically stable tomato juice. A high juice yield was obtained (97.9 ± 0.2%). The red color was preserved throughout the process. An insight is provided in the factors affecting the physical juice stability.